2018
DOI: 10.1080/09593330.2018.1493148
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the use ofMoringa oleiferaseed husks for removal of pesticide diuron from contaminated water

Abstract: Considering the need for new technologies for the removal of pesticides from the aqueous environment, the Moringa oleifera seed husks (h-MO) were investigated for the diuron adsorption from contaminated water at different temperatures and solute concentrations. The biosorbent used in this study was characterized by chemical, structural and textural analyses. The best experimental condition for the biosorption was determined by evaluating the mass of the biosorbent and the pH solution. We found a good adsorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 45 publications
4
14
0
9
Order By: Relevance
“…(B) refers to mod‐MO. Heterogeneous morphological characteristics and porous and fibrous structures can be observed in both images, in agreement with other authors . Larger pore depths were observed after the chemical and thermal treatment, caused by the destruction of fibrous structures.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…(B) refers to mod‐MO. Heterogeneous morphological characteristics and porous and fibrous structures can be observed in both images, in agreement with other authors . Larger pore depths were observed after the chemical and thermal treatment, caused by the destruction of fibrous structures.…”
Section: Resultssupporting
confidence: 91%
“…The adsorbent at this stage was denoted as mod‐MO. After separation by particle size, the particles between 600 and 500 μm were selected for the subsequent adsorption tests …”
Section: Methodsmentioning
confidence: 99%
“…It could be observed that the biosorbent presents a porous, fibrous, irregular, and heterogeneous morphology, characteristic of lignocellulosic materials, as previously verified by Alemdar and Sain . These characteristics were considered to be favorable on the adsorption of organic contaminants since it allows the access of the contaminant molecule to the internal cavities and subsequent retention …”
Section: Resultssupporting
confidence: 55%
“…23 These characteristics were considered to be favorable on the adsorption of organic contaminants since it allows the access of the contaminant molecule to the internal cavities and subsequent retention. 10,28 As shown in Figure 2a, SBH has a high carbon and oxygen content whereas a low nitrogen (38.18, 21.82, and 0.04 wt%, respectively), a result expected for an organic material. 5 It should be noted that the elements S and Cl, which are contained in the MB molecule, were not found in the spectrum in Figure 2a.…”
Section: Characterization Of the Biosorbentmentioning
confidence: 80%
See 1 more Smart Citation